Kaika yōsan no zu - Hashimoto, Chikanobu, 1838-1912. (Tōkyō : Tsujioka Bunsuke, 1886)
The Japanese print shows well-dressed women working with silkworms; a man very well dressed is supervising the women. The room is in Japanese style but still carpetted with flower design rugs. The costumes seems as noble as for the emperor and for the court ladies.
Colour woodblock oban triptych print.
Title from item.
Also available online
Keywords: Sericulture -- Japan -- Pictorial works; Silkworms -- Japan -- Pictorial works; Woodblock prints